Anti-atherogenic properties of date vs. pomegranate polyphenols: the benefits of the combination. Issue 5 (13th May 2015) - Rosenblat, Mira; Volkova, Nina; Borochov-Neori, Hamutal; Judeinstein, Sylvie; Aviram, Michael
<x xml:space="preserve">Abstract</x> MPM cholesterol content was not significantly affected by consumption of PJ or date seed extract alone. In contrast, consumption of Hallawi date fruit extract or a combination of PJ together with date fruit and date seeds extract significantly decreased macrophage cholesterol content by 12% or 28%, respectively.